The Transformation of Adaptation Specificity to Whisker Identity from Brainstem to Thalamus - Jubran, Muna; Mohar, Boaz; Lampl, Ilan (Frontiers in Systems Neuroscience, 2016)
Stimulus specific adaptation has been studied extensively in different modalities. High specificity implies that deviant stimulus induces a stronger response compared to a common stimulus. The thalamus gates sensory information to the cortex, therefore, the specificity of adaptation in the thalamus must have a great impact on cortical processing of sensory inputs. We studied the specificity of adaptation to whisker identity in the ventral posteromedial nucleus of the thalamus (VPM) in rats using extracellular and intracellular recordings. We found that subsequent to repetitive stimulation that induced strong adaptation, the response to stimulation of the same, or any other responsive whisker was equally adapted, indicating that thalamic adaptation is non-specific. In contrast, adaptation of single units in the upstream brainstem principal trigeminal nucleus (PrV) was significantly more specific. Depolarization of intracellularly recorded VPM cells demonstrated that adaptation is not due to buildup of inhibition. In addition, adaptation increased the probability of observing complete synaptic failures to tactile stimulation. In accordance with short-term synaptic depression models, the evoked synaptic potentials in response to whisker stimulation, subsequent to a response failure, were facilitated. In summary, we show that local short-term synaptic plasticity is involved in the transformation of adaptation in the trigemino-thalamic synapse and that the low specificity of adaptation in the VPM emerges locally rather than cascading from earlier stages. Taken together we suggest that during sustained stimulation, local thalamic mechanisms equally suppress inputs arriving from different whiskers before being gated to the cortex.